Theracurmin may be a therapeutic option for elderly patients with Alzheimer's disease: A 6‐month retrospective follow‐up study. (31st December 2021) - Dost, Fatma Sena; Kaya, Derya; Erken, Neziha; Bulut, Esra Ateş; Ontan, Mehmet Selman; Aydın, Ali Ekrem; Isik, Ahmet Turan
Abstract: Background: Therapeutic options for Alzheimer's Disease (AD) treatment are highly limited and success rate in new molecules under investigated has been disappointing so that agents with various mechanisms represent a promising therapeutic opportunity. Among these, Theracurmin, a very highly absorbable curcumin formulation, was shown to improve memory and attention in non‐demented people. We aimed to investigate the effect of Theracurmin on the disease course in elderly patients with mild cognitive impairment (MCI) and AD. Method: This is a retrospective follow up study on 93 consecutive elderly patients with MCI or AD. All patients underwent Comprehensive geriatric assessment (CGA), including Mini Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), clock‐drawing test, trail making, activities of daily living (ADL), at baseline and end of the sixth month. Nineteen of 52 patients with AD and 17 of 41 patients with MCI were treated with Theracurmin 180 mg/day (PO). All AD patients were also treated with an acetylcholinesterase inhibitor. Result: During the follow up period it was observed that MMSE or MOCA and instrumental ADL (IADL) scores declined in AD patients without treating with Theracurmin (p=0.001; 0.011; 0.004, respectively), whereas these scores remained stable in those with Theracurmin. Furthermore, this stabilization in the IADL was also observed in MCI patients treated with Theracurmin, but not in those without Theracurmin. During the follow‐up, three of MCI patients who did not receive Theracurmin progressed to AD, whereas it was only one patient in those who received it. No discontinuation of Theracurmin therapy was observed. Conclusion: Theracurmin seems to be a therapeutic option for elderly patients with AD and MCI because of providing stabilization of the disease course by preventing progressive loss in cognitive functions and ADLs. Further prospective, multicenter, community‐based studies are needed to confirm these promising findings.